Studi Jenis Nyamuk Anopheles pada Tempat Perindukannya di Desa Rukoh Kecamatan Syiah Kuala Kota Banda Aceh - Widya Sari; Tjut Mariam Zanaria; Elita Agustina (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
The research on species of  Anopheles’ breeding places has been carried out at Desa Rukoh in the District of Syiah Kuala, Banda Aceh from February to June 2007. The aim of the research was to identify species of Anopheles’  breeding places at Desa Rukoh. In this research, the purposive sampling method has been implemented to obtain the samples from ten different locations around Desa Rukoh. Data collection was conducted by catching the larva at breeding places and catching the adult Anopheles  trapped by using Aspirator and Light Trap. CCD microscope was  used to identify the species of Anopheles. Furthermore, the data were analyzed by using the descriptive approaches. Based on laboratory analysis, it has been identified that three species of Anopheles namely, An. subpictus, An. vagus,  and An. sundaicus. The breeding places of Anopheles  at Desa Rukoh were ponds, buffalo’s trash dam, ex man’s footprint, ditches and swamp.